ELECTIVE PERCUTANEOUS CORONARY INTERVENTIONS-A COMPARISION OF EFFICACY OF CLOPIDOGREL AND PRASUGREL - ., Shahzeb; Ali, Nasir; Hadi, Abdul; shah, Ibrahim; Gul, Adnan Mehmood; Ali, Jabar; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Percutaneous coronary interventions are almost always preceded by the loading dose of platelets inhibiter drugs such as clopidogrel or prasugrel and followed by maintenance therapy to decrease the mortality and morbidity due to stent thrombosis. This study was conducted to compare the efficacy of clopidogrel and prasugrel for inhibiting platelet aggregation among patients undergoing elective percutaneous coronary intervention. Methods: This randomized controlled trial study was done in Department of Cardiology, Postgraduate Medical Institute Govt. Lady Reading Hospital Peshawar. A total of 148 patients were randomly allocated to either group-A containing 74 patients using clopidogrel or group-B containing 74 patients using prasugrel Results:. Group-A had 55 (74.3%) male and 19 (25.7%) females while group-B had 56(75.7%) males and 18(24.3%) females (p=0.85). Mean age was 54.9±11.2 years in group-A and was 57.7±8.7 years in group-B (p=0.09). Mean body weight was 71.8±6.4 Kg in group-A and 70.8±6.3 Kg in group-B (p=0.35). Mean Baseline platelet aggregation before drug administration was 10.43±1.9 ohm in group-A while 10.12±2.2 ohm in group-B (p=0.36). Mean Follow up platelet aggregation 6 hours after drug administration was 5.88±2.9 in group-A while it was 3.47±1.8 ohm in group-B (p=0.001). Mean Difference between basal and follow up platelet aggregation ±SD was 52.9649±24.77 in group-A while it was 82.25±14.34 in group-B (p=0.001). 63(85.15%) of group-A had inhibition of platelets aggregation >10% as compare to 72(97.3%) of group-B had inhibition of platelets aggregation >10% (p=0.009). Conclusion: Prasugrel is more efficacious than clopidogrel in term of inhibition of platelets aggregation. Keywords: Clopidogrel, prasugrel, platelets aggregation